2018
DOI: 10.1021/acs.macromol.8b02033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Property and Flame Retardancy via Intramolecular 5-Membered Ring Hydrogen Bond-Forming Amide Functional Benzoxazine Resins

Abstract: Polybenzoxazines containing an ortho-amide group in the backbone with a significant degree of aromaticity have been synthesized and characterized in this study. This class of materials makes use of smart chemistry to be able to readily process the monomer and later transform from polybenzoxazine into polybenzoxazole. All the benzoxazine monomers studied contain amide groups that form 5-membered intramolecular hydrogen bonds with the oxazine rings. Systematic manipulation of the diamine structure has allowed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…Among these thermosets obtained in this study, poly(NAR-a/DGEBA) showed the lowest ammability, supported by its very low HRC and THR values, indicating that the higher degree of cross-linking can enhance the ame retardancy of epoxy-related thermosetting systems. Though the HRC value of poly(NAR-a/DGEBA) is higher than many polybenzoxazines with excellent ame retardancy, 41,42 it is substantially lower than the traditional and some recently reported high-performance epoxy thermosetting systems. 5 Therefore, the NAR-a/DGEBA thermosetting system may have great potential in applications that benet both high thermal stability and low ammability.…”
Section: Polymerization Behaviors Of Benzoxazine and Benzoxazine/ Epomentioning
confidence: 77%
“…Among these thermosets obtained in this study, poly(NAR-a/DGEBA) showed the lowest ammability, supported by its very low HRC and THR values, indicating that the higher degree of cross-linking can enhance the ame retardancy of epoxy-related thermosetting systems. Though the HRC value of poly(NAR-a/DGEBA) is higher than many polybenzoxazines with excellent ame retardancy, 41,42 it is substantially lower than the traditional and some recently reported high-performance epoxy thermosetting systems. 5 Therefore, the NAR-a/DGEBA thermosetting system may have great potential in applications that benet both high thermal stability and low ammability.…”
Section: Polymerization Behaviors Of Benzoxazine and Benzoxazine/ Epomentioning
confidence: 77%
“…6,7 The most promising approach toward resolving the flammability issue is imparting the flame retardancy feature to PET materials. [8][9][10] The effective and durable implementation of flame retardancy in PET materials can be achieved by the chemical grafting of functional monomers to the PET chains. 3,11 Nowadays, flame retardants need to fulfill higher requirements, 11 for example, to be halogen-free, nontoxic, and environmentally friendly, 12 which oriented current research in that direction.…”
Section: Introductionmentioning
confidence: 99%
“…As a new class of thermosets, polybenzoxazines have drawn great attention from academic as well as industrial communities for their outstanding characteristics compared with other thermosets, such as epoxies, phenolics, bismaleimides and even polyimides. Notable advantages include their remarkable molecular design flexibility [1][2][3][4][5][6][7], excellent thermal and mechanical properties [8], high char yield [9], excellent flame retardancy [10][11][12][13][14], autocatalysis for ring-opening polymerization [15], near-zero shrinkage upon polymerization [16,17], excellent electrical properties [18][19][20][21][22][23][24][25] and surface energy lower than polytetrafluoroethylene [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%